Cerebellar abiotrophy in an Icelandic horse - Sanni Hansen; Emil Olsen; Marie Raundal; Jørgen Steen Agerholm (Acta Veterinaria Scandinavica, 2022)
Abstract Background Cerebellar abiotrophy (CA) is an uncommon hereditary neurodegenerative disorder affecting the cerebellar Purkinje cells. Equine CA has been reported in several breeds, but a genetic etiology has only been confirmed in the Arabian breed, where CA is caused by an autosomal recessive mutation. Case presentation. Clinical and histological findings consistent with CA are reported in an 8.5-month-old Icelandic filly. The filly showed a perceived sudden onset of marked head tremor, incoordination, ataxia, lack of menace response and a broad-based stance. Cerebrospinal fluid, hematological and biochemical findings were all within the normal range, ruling out several differential diagnoses. Post mortem histopathological examination revealed Purkinje cell degeneration accompanied by astrogliosis. Assessment of the filly’s pedigree revealed that its parents shared a common ancestor. Conclusions To the authors’ knowledge, this is the first report of CA in the Icelandic breed. The identification of a common parental ancestor makes autosomal recessive inheritance of CA in this filly possible, but this would need to be confirmed by further studies. Veterinarians and breeders working with Icelandic horses should be aware of this condition and report suspected cases in order to support genetic investigation.